PENGGUNAAN TEKHNIK BLUEPRINT PADA PEMODELAN OBJEK 3D - Fauzi, Muhammad (STMIK KAPUTAMA, 2019)
3D object is a manipulation of objects that have length, width and height or use 3 coordinate axes namely x, y and z. 3D objects look so real because they are made of real things and this 3D object is popular with all circles, because the sharp effects and high color resolution make the 3D look more real and beautiful. But not many people know how to make it and that knowledge is hard to come by. Some sources cannot be expected so detailed to share their knowledge. Therefore, the writer wants to share the knowledge that is gained from experience and to become an addition. There are several techniques used to maximize and facilitate sharp and accurate 3D object modeling, one of the important of these techniques is the Blueprint, Blueprint is a design drawing or sketch of an object in the form of 2 dimensions, consisting of images of side objects, front view , looks above and looks back, this allows us to make the blueprint as the main reference and capital for building 3D objects in great detail and because also 3D textures or object shapes only follow sketches that are displayed only from the blueprint, the 3dsmax blueprint application can also help animators in making all the desired models, a blueprint can be obtained through a site that is already available and can also be self-created through the design drawings which will be scanned to the computer with jpeg format with pixel resolution that must be above 760 x 680 so that the image looks clearer and easier for the modeling process 3D object.